Changing the topology of protein backbone: the effect of backbone cyclization on the structure and dynamics of a SH3 domain - Schumann, Frank H.; Varadan, Ranjani; Tayakuniyil, Praveen P.; Grossman, Jennifer H.; Camarero, Julio A.; Fushman, David (Frontiers in Chemistry, 2015)
Understanding of the effects of the backbone cyclization on the structure and dynamics of a protein is essential for using protein topology engineering to alter protein stability and function. Here we have determined, for the first time, the structure and dynamics of the linear and various circular constructs of the N-SH3 domain from protein c-Crk. These constructs differ in the length and amino acid composition of the cyclization region. The backbone cyclization was carried out using intein-mediated intramolecular chemical ligation between the juxtaposed N- and the C-termini. The structure and backbone dynamics studies were performed using solution NMR. Our data suggest that the backbone cyclization has little effect on the overall three-dimensional structure of the SH3 domain: besides the termini, only minor structural changes were found in the proximity of the cyclization region. In contrast to the structure, backbone dynamics are significantly affected by the cyclization. On the subnanosecond time scale, the backbone of all circular constructs on average appears more rigid than that of the linear SH3 domain; this effect is observed over the entire backbone and is not limited to the cyclization site. The backbone mobility of the circular constructs becomes less restricted with increasing length of the circularization loop. In addition, significant conformational exchange motions (on the sub-millisecond time scale) were found in the N-Src loop and in the adjacent β-strands in all circular constructs studied in this work. These effects of backbone cyclization on protein dynamics have potential implications for the stability of the protein fold and for ligand binding.